In exceptional times: The covid-19 pandemic, parenting and the disabling effects of mental health difficulties - Flynn, Susan (My University, 2025)
Increasing uptake of the metaphor of a ‘tsunami’ of mental health problems related to covid 19, reflects widespread concern for pandemic related mental distress. Mental health may be compromised by such things as loneliness and depression linked to social isolation, as well as fear of infection from coronavirus. Of interest to question is the veracity of this concern and how the alleged decline in mental wellness might affect one of society’s most important issues: Namely, the issue of parenting. Owing to the novel nature of this subject matter, scoping review was selected to substantiate critical commentary in this paper surrounding parenting, the covid 19 pandemic and the disabling effects of mental health difficulties. Findings suggest that there is no linear, formulaic or conclusive relationship between the pandemic, mental health and parenting. Rather, present discourses, such as those that embrace a tsunami metaphor, ought to attain more nuance and balance, in the context of protective factors, opportunities and strengths also at play.
PUBLISHED
https://doi.org/10.1080/13575279.2024.2353683
Keywords: covid 19, pandemic, mental health, parenting, children